Hybrid DE-PSO algorithm for solving nonlinear equations of SHEPWM based wind power conversion - Abdelgoui, Rim Feyrouz; Taleb, Rachid; Namoune, Abdelhadi; Saidi, Hemza; Mansour, Noureddine (STUDIES IN ENGINEERING AND EXACT SCIENCES, 2024)
The novel power conversion for wind energy conversion systems is presented in this article has developed by a new hybrid multilevel inverter (HMLI)  topologies including fewer switches, and an excellent output voltage spectrum. Selective Harmonic elimination In order to achieve precise harmonic control for hybrid multilevel inverter (HMLI), SHEWM can eliminate certain low order harmonics by solving nonlinear transcendental equations to determine the switching angles beforehand. This research proposes a hybrid DE-PSO algorithm for PWM inverter switching angle selection. The wind energy conversion systems(WECS) consisted of an isolated load-connected innovative multilevel inverter, a diode bridge rectifier, a conventional boost converter, and a permanent magnet synchronous generator (PMSG). It has been demonstrated that the power conversion using multilevel DC to AC converter has improved power quality, efficiency, and voltage utilization, it is noted that the intended system functions with little harmonic content and that the power produced by the permanent magnet synchronous generator is successfully transmitted to the load. MATLAB Simulink has been used to investigate the integration of wind energy conversion systems.